PERCEPTIONS AND FORMS OF ACTION OF ELEMENTARY SCHOOL TEACHERS IN FKONT OF SCHOOL BULLYING - Lima, Danyelle Shmith de; Tenorio Pereira, Rosana Aparecida; Francisco, Marcos Vinicius [UNESP] (Centro Univ Nove Julho, 2020)
The present research had as objective to analyze the perceptions and forms of action of primary school teachers in front of school bullying. As methodological procedures, semi-structured interviews were carried out with the teachers of four schools, each one being located in different regions, in a small municipality in the interior of the Sao Paulo, Brazil. The research is qualitative, of the multiple case study type. According to the report of the teachers, the schools courtyards are the places where bullying occurs most often, followed by classrooms. Of the situations of systematic intimidation experienced, those linked to the physical and corporal structure of the victims predominated. Although most of the participants mentioned contact with bullying situations, in the pedagogical praxis or in the educational institution where they work, few developed any intervention activity, due to lack of training or support from schoolmanagement.
Keywords: School bullying; Elementary school; Pedagogical praxis